2009
DOI: 10.1080/16513860902900136
|View full text |Cite
|
Sign up to set email alerts
|

Audiological profiles and gjb2, gjb6 mutations: A retrospective study on genetic and clinical data from 2003 to 2008

Abstract: In many world populations, mutations in the GJB2 gene (codifyng for Connexin 26) are the most common causes of autosomal recessive non-syndromic hearing loss and account for approximately 50% of cases. To date, more than 100 (dominant or recessive) mutations have been identified (The Connexin Deafness Homepage, 2009) and differences in frequency and distribution across the world are significant. In European and American Caucasian populations, the 35delG is the most common mutation found to account for nearly 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
4
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 25 publications
3
4
0
Order By: Relevance
“…In total, 19 persons (24%) in the present study were homozygotes for the 35delG mutation and among these 16 (84%) had a severe or profound hearing impairment. Furthermore, in an Italian study, Berto et al [12] showed that 80% of the homozygotes for CÂ35del had a severe or profound hearing impairment, hence the same result as in this study.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In total, 19 persons (24%) in the present study were homozygotes for the 35delG mutation and among these 16 (84%) had a severe or profound hearing impairment. Furthermore, in an Italian study, Berto et al [12] showed that 80% of the homozygotes for CÂ35del had a severe or profound hearing impairment, hence the same result as in this study.…”
Section: Discussionsupporting
confidence: 86%
“…Several studies in Europe have shown a high rate of homozygous, compound heterozygous and heterozygous CÂ26 mutations and polymorphisms among hearing-impaired persons [12]. The frequencies of CÂ26 mutations and polymorphisms described on The Connexins and Deafness homepage (http:// davinci.crg.es/deafness) found among hearing-impaired persons in Europe varies between 30% and 50% in unselected populations [13,14].…”
Section: Introductionmentioning
confidence: 98%
“…This suggests a lower involvement in Eastern Sicily of the c.−23+1G>A allele. Other studies highlighted percentages of this allele ranging from 2.89% to <1% (Cryns et al., ; Snoecks et al., ; Berto et al., ).…”
Section: Discussionmentioning
confidence: 95%
“…In our study, the HL of c.35delG homozygous patients was profound in 71.5% (20/28). In the past, this genotype was associated with a profound HL in 65.79% and 64% of patients (Snoeckx et al., ; Berto et al., ). Our findings overlap those obtained by Martines et al (), who found HL in 75% of patients homozygous for the c.35delG allele.…”
Section: Discussionmentioning
confidence: 99%
“…This generates deploarization, which opens Ca 2+ channels. When calcium enters, neurotransmitters are realeased onto the afferent nerve [9] A B lating K + homeostasis during the normal function of hearing process, and which its mutations are responsible for most deafness cases [7]. Moreover, gap junction beta 2 is found in the long arms of chromosome 13 in positions 11 and 12, and has a length of 5.5 kilobases.…”
Section: The Gjb2 Gene Cx2 and The Hearing Processmentioning
confidence: 99%